HR process safety & security in the industry 4.0. era - Kemendi, Agnes (Bánki Közlemények, 2021)
Digital ecosystems embrace the day-to-day life. Internet is embedded to products and services. Artificial intelligence tools are in support of operational processes of companies. The new technologies have redefined the floor of the work scene. The publication will present the impact of the new technologies on human resources management in the ever-changing world, introduce what artificial intelligence is about and how the possibilities of artificial intelligence can be unleashed in human resources management. The publication will describe the new possibilities of the ways of working in human resources management in light of the digital transformation and gives an overview of the expected control measures in the HR function that ensure the safety and security of the process. Within the era of industry 4.0 the publication discusses the so called HR 4.0. Phenomenon. Artificial intelligence in HR function has certainly its benefits and barriers. Those entities who go with the flow of the digital organization engage in completely new ways of working that will enhance their long-term competitiveness. As a result of digital transformation companies can easier concentrate on core value added activities that generate real value. The new phenomena reshape the set of jobs: job functions have been eliminated as a result of automation and on the other hand new ones have been created, new job roles appear in particular in the IT department. The commitment of employees in the change management process is inevitable that place the corporate learning to a new level. The role of safety and security measures in the operational environment continues to stay the fundamental pillar of a successful organization.